Manajemen Produksi Channel Youtube LDII TV dalam Penguatan Dakwah Digital - Sri Wulandari; Fakhrur Rozi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
LDII TV is a Youtube Channel managed by the Indonesian Islamic Propagation Institute (LDII). In the increasingly advanced development of technology, preaching is carried out digitally through a digital platform, namely Youtube. This study aims to understand the media production management used by LDII TV, explain the programs, obstacles, and opportunities and hopes in LDII TV's digital preaching. This study uses a qualitative approach with a case study research method. The method in this study was collected through interviews with LDII TV policy makers and LDII congregations, as well as observations on the LDII TV Youtube Channel account. Additional data was obtained from books, documents, journal articles, and other sources. The results of this study indicate that LDII TV's production management uses the POAC theory (Planning, Organizing, Actuating, and Controlling) proposed by George R. Terry. In addition, this study also found obstacles and solutions in every production process that runs such as technical errors and lack of Human Resources (HR), as well as opportunities and hopes in improving content and HR for the existence of LDII TV in strengthening digital preaching.